2019
DOI: 10.1111/hdi.12804
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility and safety of sharp recanalization for superior vena cava occlusion in hemodialysis patients: A retrospective cohort study

Abstract: Introduction: Hemodialysis catheter-related superior vena cava (SVC) occlusions can cause considerable morbidity for patients and be challenging to treat if refractory to conventional guide wire transversal. This pilot study assessed the feasibility and safety of sharp recanalization of SVC occlusion in hemodialysis patients.Methods: This study retrospectively enrolled hemodialysis patients treated in West China Hospital diagnosed with SVC occlusion who failed traditional guide wire transversal from January 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 23 publications
0
11
1
Order By: Relevance
“…Recently, using different methods and tools to cross the chronically occluded segments have been called sharp recanalization. The most common method for sharp recanalization uses a stiff guide wire, PTCD puncture needle, and RUPS100 and transseptal needle (1,7). Common complications in this type of surgical procedure include pain, bleeding associated with vein varicosities More severe complications include malignant arrhythmia, hydrothorax, hydropericardium, and especially pericardial tamponade, for which there is no efficient hemostasis method, posing a serious threat to life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, using different methods and tools to cross the chronically occluded segments have been called sharp recanalization. The most common method for sharp recanalization uses a stiff guide wire, PTCD puncture needle, and RUPS100 and transseptal needle (1,7). Common complications in this type of surgical procedure include pain, bleeding associated with vein varicosities More severe complications include malignant arrhythmia, hydrothorax, hydropericardium, and especially pericardial tamponade, for which there is no efficient hemostasis method, posing a serious threat to life.…”
Section: Discussionmentioning
confidence: 99%
“…There are some studies have reported the techniques including sharp recanalization and puncture superior vena cave. However, the patients in these reports suffered from vascular occlusion either superior vena cava or brachiocephalic vein individually, while inferior vena cava is often spared entirely (1,2). But there are no reports of rebuilding vascular access in cases of multiple central vein occlusion involving the superior and inferior vena cava with the conditions occur bilaterally and the presence of severe edema.…”
Section: Introductionmentioning
confidence: 99%
“…Transhepatic venipuncture and translumbar venipuncture are also treatment methods for refractory SVC obstruction, but have the disadvantages of poor tolerance and a high risk of infection. For patients refractory to conventional guidewire transversal, SVC sharp recanalization may be an option, and its application in SVC occlusion has been increasingly reported in recent years (3,4).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with a CVC may experience endothelial inflammation, fibrosis, and thrombus formation due to blood flow disturbances and mechanical stimulation caused by the insertion of a hemodialysis catheter, leading to intimal hyperplasia and occlusion of the SVC lumen. If the position of the catheter tip proximal to the right atrium, it may develop chronic occlusion of the SVC, or SVC syndrome due to the above reaction (2,3). SVC occlusion can be treated via open surgical or endovascular repair.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been reported that refractory CVO cannot be recanalized using traditional catheter and guidewire techniques (7,8). Therefore, sharp recanalization with more procedure-related complications, such as a Chiba needle, the stiff end of a hydrophilic wire, and transseptal needle, has been gradually applied to the treatment of challenging CVO (9)(10)(11). Currently, blunt impingement for refractory CVO is rarely reported.…”
Section: Introductionmentioning
confidence: 99%